Turbostratified microporous structure soft carbon negative electrode material and preparation method thereof, and sodium battery
Through the crushing, pre -oxidation, carbonization and water heat treatment of smoke -free coal, prepare the chaotic micro -pore structure soft carbon negative materials, solve the problem of low energy density of sodium batteries and short circulation life, and achieve efficient sodium ion storage and stability Battery performance.
Patent Information
- Application Number
- CN202211725081.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The existing sodium batteries have low energy density, small battery capacity, short charging and discharge cycle life, and it is difficult to deintercalate sodium ions in sodium batteries.
The chaotic micro -pore structure soft carbon negative material is used. The preparation method includes crushing, pre -oxidation, carbonization, and water heat treatment of smokeless coal with a gray less than 3 % to form a rich chaotic micro -pore structure to improve the sodium ion storage capacity.
The first Kuron efficiency and cycle stability of sodium batteries improved, reducing costs and adapting to market demand.
Smart Images

Figure CN116119647B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrode materials for sodium batteries, and in particular to a soft carbon negative electrode material with a turbostratic microporous structure and a preparation method thereof, and a sodium battery. Background Art
[0002] As a cheap and efficient means of energy storage, battery technology has been widely studied and gradually matured. Among them, lithium batteries are currently a relatively mature type, with the advantages of high energy density, long service life, good safety and low environmental pollution. However, with the increasing application of lithium batteries, the problem of limited mineral reserves of lithium sources has become increasingly prominent, which has led to the gradual increase in the price of lithium mineral resources and their derivatives. People are in urgent need of a new energy battery technology that can replace lithium batteries. Sodium, as an abundant mineral element, has wide availability and low cost. The use of sodium in batteries is expected to meet the needs of large-scale grid energy storage to solve the increasingly prominent problem of limited mineral reserves of lithium sources.
[0003] At present, sodium batteries still have problems such as low energy density, small battery capacity, and short charge and discharge cycle life. In order to solve this series of problems, people have conducted in-depth research on the positive electrode, negative electrode, electrolyte materials and their assembly structure of sodium batteries. In the research section of negative electrode materials, people have discovered negative electrode materials with better performance, such as carbon materials, nitride materials, silicon and silicide materials, and various metal alloys. Among them, carbon materials have significant characteristics such as low price, wide source, and excellent conductivity, and have good applications in lead-acid batteries, lithium manganese batteries, lithium cobalt batteries and other systems. However, due to the small interlayer spacing of carbon materials and the fact that the radius of sodium ions is much larger than that of lithium ions, it is difficult for traditional carbon materials to be deintercalated and deintercalated when used in sodium batteries. Therefore, people will improve carbon materials to better adapt to the deintercalation and deintercalation of sodium ions.
[0004] For example, patent CN104377346A discloses a method for preparing a modified graphite negative electrode material for a sodium ion battery, and specifically discloses preparing a paste of graphite oxide by the Hummer method; then using asphalt, phenolic resin or glucose as a carbon precursor to coat the graphite oxide, and finally subjecting the carbon precursor-coated graphite oxide to carbonization heat treatment under an inert gas atmosphere. This method has the advantages of simple preparation process, wide source of raw materials, and suitability for large-scale industrial production. The obtained modified graphite negative electrode material has a carbon layer spacing of not less than 0.36nm and a carbon coating layer thickness of 0.01-1μm.
[0005] However, the traditional approach is to obtain a modified graphite negative electrode material with a coating layer by using the Hummer method, which will hinder the advantages of the carbon material itself, not only resulting in high costs, but also still having poor first coulombic efficiency and cycle stability. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a low-cost turbostratic microporous structure soft carbon negative electrode material and a preparation method thereof, and a sodium battery.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a turbostratic microporous structure soft carbon negative electrode material comprises the following steps:
[0009] Obtain anthracite with an ash content of less than 3%;
[0010] Grinding the anthracite to obtain anthracite powder;
[0011] Pre-oxidizing the anthracite powder to obtain anthracite powder doped with oxygen-containing functional groups;
[0012] Mixing the anthracite powder doped with oxygen-containing functional groups with an alkali solution to obtain an anthracite mixed solution;
[0013] Carrying the anthracite mixture through a step-temperature carbonization process to obtain anthracite carbonized material;
[0014] Washing the anthracite carbonized material with water until it becomes neutral to obtain porous anthracite;
[0015] Mixing the porous anthracite with an alkaline solution to obtain a first porous anthracite mixed solution;
[0016] adding an acid solution to the porous anthracite mixed liquid to obtain a second porous anthracite mixed liquid;
[0017] Performing a hydrothermal reaction on the porous anthracite second mixed liquid to obtain a porous anthracite third mixed liquid;
[0018] filtering the porous anthracite third mixed liquid to obtain a precipitate;
[0019] The precipitate is freeze-dried to obtain the turbostratic microporous structure soft carbon negative electrode material.
[0020] In some other embodiments, the anthracite powder is oxidized in an air atmosphere at 400° C. to 500° C. for 2 h to 5 h, and the air pressure is controlled to be 3 KPa to 5 KPa.
[0021] In some other embodiments, the step temperature carbonization conditions are: in an inert atmosphere, the temperature is increased to 800°C~1000°C at 3°C~8°C / min, then the temperature is increased to 1000°C~1400°C at 1°C~2°C / min and kept at this temperature for 2h~5h, then the temperature is decreased to 800°C~1000°C at 3°C~5°C / min, and then the temperature is decreased to room temperature at 5°C~8°C / min.
[0022] In some other embodiments, the particle size of the anthracite powder is 5 μm to 30 μm.
[0023] In some other embodiments, the mass ratio of the anthracite powder doped with oxygen-containing functional groups to the alkaline solution is 1:1 to 1:5.
[0024] In some other embodiments, the conditions of the heat preservation hydrothermal reaction are: temperature 100°C to 260°C, time 8h to 24h.
[0025] In some other embodiments, the acid includes at least one of sulfuric acid, nitric acid, hydrofluoric acid and hydrochloric acid.
[0026] In some other embodiments, the alkaline solution includes at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide.
[0027] A soft carbon negative electrode material with a turbostratic microporous structure is obtained by using the preparation method of the soft carbon negative electrode material with a turbostratic microporous structure described in any of the above embodiments.
[0028] A sodium battery comprises the turbostratic microporous structure soft carbon negative electrode material described in any one of the above embodiments.
[0029] Compared with the prior art, the present invention has at least the following advantages:
[0030] 1. The preparation method of the above-mentioned soft carbon negative electrode material with a microporous structure of a turbostratic layer can dope the anthracite powder with oxygen-containing functional groups by pre-oxidizing the anthracite powder. In this way, the doped oxygen-containing functional groups can increase the interlayer spacing of the anthracite, which is helpful to inhibit the directional growth of graphene domains during the subsequent step temperature carbonization to obtain a richer turbostratic microporous structure. The added alkaline solution can increase the porosity of the anthracite powder doped with oxygen-containing functional groups, and then step temperature carbonization is performed, which is conducive to the formation of a more uniform and appropriately spaced soft carbon negative electrode material, thereby forming a rich turbostratic microporous structure. Therefore, the hard carbon soft carbon negative electrode material can accommodate more sodium ions, that is, provide more sodium storage active sites for sodium ions, thereby enhancing the reversible capacity of the sodium battery, and then improving the first coulombic efficiency and cycle stability of the sodium battery. In addition, compared with the traditional method, the present application reduces the preparation process of the coating layer, avoids the addition of the coating layer material, thereby saving costs, and gives play to the advantages of carbon materials in sodium batteries to better meet market needs.
[0031] 2. The preparation method of the above-mentioned soft carbon negative electrode material with a turbostratic microporous structure selects anthracite with an ash content of less than 3% as the raw material to ensure that the impurities in the anthracite are moderate. This helps to construct a soft carbon negative electrode material with a rich turbostratic microporous structure to increase the capacity of the soft carbon negative electrode material to accommodate sodium ions, thereby providing a good guarantee for the first coulombic efficiency and cycle performance of the sodium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 This is a flow chart of a method for preparing a turbostratic microporous structure soft carbon negative electrode material according to an embodiment of the present invention;
[0034] Figure 2 This is a SEM image of the turbostratic microporous structure soft carbon negative electrode material of Example 1 of the present invention;
[0035] Figure 3 This is a test graph of the first coulombic efficiency of the turbostratic microporous structure soft carbon negative electrode material of Example 1 of the present invention;
[0036] Figure 4 for Figure 3 The enlarged view of point A in the middle;
[0037] Figure 5 for Figure 3 The enlarged view of point B in the middle;
[0038] Figure 6 This is a test chart of the capacity retention rate of the turbostratic microporous structure soft carbon negative electrode material of Example 1 of the present invention;
[0039] Figure 7 This is a test chart of the capacity retention rate of the soft carbon negative electrode material of Comparative Example 1 of the present invention;
[0040] Figure 8 This is a test chart of the capacity retention rate of the soft carbon negative electrode material of Comparative Example 2 of the present invention;
[0041] Fig. 9 This is a test chart of the capacity retention rate of the soft carbon negative electrode material of comparative example 3 of the present invention. DETAILED DESCRIPTION
[0042] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0043] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to suppress the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0045] The present application provides a method for preparing a soft carbon negative electrode material with a turbostratic microporous structure, comprising the steps of obtaining anthracite with an ash content of less than 3%; pulverizing the anthracite to obtain anthracite powder; pre-oxidizing the anthracite powder, doping the anthracite powder with oxygen-containing functional groups to obtain anthracite powder doped with oxygen-containing functional groups; mixing the anthracite powder doped with oxygen-containing functional groups with an alkaline solution to obtain an anthracite mixed solution; carbonizing the anthracite mixed solution at a step temperature to obtain an anthracite carbonized material; and washing the anthracite powder with water. The anthracite carbonization material is treated to neutrality to obtain porous anthracite; the porous anthracite is mixed with an alkaline solution to obtain a porous anthracite first mixed liquid; an acid solution is added to the porous anthracite mixed liquid to obtain a porous anthracite second mixed liquid; the porous anthracite second mixed liquid is subjected to a hydrothermal reaction at a heat preservation temperature to obtain a porous anthracite third mixed liquid; the porous anthracite third mixed liquid is filtered to obtain a precipitate; the precipitate is freeze-dried to obtain the turbostratic microporous structure soft carbon negative electrode material.
[0046] The preparation method of the above-mentioned soft carbon negative electrode material with a microporous structure of a turbostratic layer can dope the anthracite powder with oxygen-containing functional groups by pre-oxidizing the anthracite powder. In this way, the doped oxygen-containing functional groups can increase the interlayer spacing of the anthracite, which is helpful to inhibit the directional growth of graphene domains during the subsequent step temperature carbonization to obtain a richer turbostratic microporous structure. The added alkaline solution can increase the porosity of the anthracite powder doped with oxygen-containing functional groups, and then step temperature carbonization is performed, which is conducive to the formation of a more uniform and appropriately spaced soft carbon negative electrode material, thereby forming a rich turbostratic microporous structure. Therefore, the hard carbon soft carbon negative electrode material can accommodate more sodium ions, that is, provide more sodium storage active sites for sodium ions, thereby enhancing the reversible capacity of the sodium battery, and then improving the first coulombic efficiency and cycle stability of the sodium battery. In addition, compared with the traditional method, the present application reduces the preparation process of the coating layer, avoids the addition of the coating layer material, thereby saving costs, and gives play to the advantages of carbon materials in sodium batteries to better meet market needs. Furthermore, since anthracite with an ash content of less than 3% is selected as the raw material to ensure that the impurities in the anthracite are moderate, this helps to construct a soft carbon negative electrode material with a rich chaotic layer microporous structure, so as to improve the capacity of the soft carbon negative electrode material to accommodate sodium ions, thereby providing a good guarantee for the first coulombic efficiency and cycle performance of the sodium battery.
[0047] See also Figure 1 In order to better understand the technical solution and beneficial effects of the present application, the present application is further described in detail below in conjunction with specific examples. A method for preparing a turbostratic microporous structure soft carbon negative electrode material in one embodiment includes some or all of the following steps:
[0048] S101. Obtain anthracite with an ash content of less than 3%.
[0049] It can be understood that low ash content refers to anthracite with less impurity content. If the impurity content is high, the impurity content of the subsequent soft carbon negative electrode material with a microporous structure is not conducive to the reversible embedding and extraction of sodium ions during the charge and discharge process. That is to say, the soft carbon negative electrode material with a microporous structure with a high impurity content will have an inhibitory effect on sodium ions and affect the transmission rate of sodium ions. However, the applicant has found that when the ash content of anthracite is less than 3%, the pores constructed by a small amount of impurities are uneven, which can enrich the microporous structure of the chaotic layer. That is to say, when the ash content is less than 3%, the impurities in the anthracite are relatively moderate, which helps to construct a rich soft carbon negative electrode material with a microporous structure of the chaotic layer, so as to improve the capacity of the soft carbon negative electrode material to accommodate sodium ions, thereby providing a good guarantee for the first coulombic efficiency and cycle performance of the sodium battery.
[0050] S102, pulverizing the anthracite to obtain anthracite powder, so as to obtain anthracite powder with a small particle size, which is helpful for subsequent processing to ensure that a soft carbon negative electrode material with a rich chaotic layer microporous structure is obtained. Further, in some other embodiments, the particle size of the anthracite powder is 5μm to 30μm.
[0051] S103, pre-oxidizing the anthracite powder to dope the anthracite powder with oxygen-containing functional groups to obtain anthracite powder doped with oxygen-containing functional groups.
[0052] It can be understood that by pre-oxidation treatment of anthracite powder, the anthracite powder can be doped with oxygen-containing functional groups, so that the doped oxygen-containing functional groups can increase the interlayer spacing of the anthracite, which helps to inhibit the directional growth of graphene domains during subsequent step temperature carbonization to obtain a richer chaotic layer microporous structure. It is worth mentioning that the chaotic layer microporous structure of the present application refers to the interlayer spacing being the same, and the pores of each layer are uneven, so that the chaotic layer microporous structure soft carbon negative electrode material can present a short-range ordered and long-range disordered structure, so that the hard carbon soft carbon negative electrode material can accommodate more sodium ions, that is, provide more sodium storage active sites for sodium ions, thereby enhancing the reversible capacity of the sodium battery, and then improving the first coulombic efficiency and cycle stability of the sodium battery.
[0053] S104, mixing the anthracite powder doped with oxygen-containing functional groups with an alkali solution to obtain an anthracite mixed solution, the added alkali solution can increase the porosity of the anthracite powder doped with oxygen-containing functional groups, that is, to achieve pore formation on the surface of the anthracite powder doped with oxygen-containing functional groups, which is helpful for subsequent step temperature carbonization, and the surface pores can help heat transfer, so that the anthracite mixed solution can be quickly step temperature carbonized, which helps to construct a rich chaotic layer microporous structure. Further, in some other embodiments, the mass ratio of the anthracite powder doped with oxygen-containing functional groups to the alkali solution is 1:1 to 1:5.
[0054] S105, subjecting the anthracite mixture to step-temperature carbonization to obtain anthracite carbonized material.
[0055] It can be understood that by subjecting the anthracite mixture to step-temperature carbonization, it is beneficial to form a relatively uniform and appropriately spaced soft carbon negative electrode material, so as to realize the construction of the micropore structure inside the anthracite, thereby helping to form a rich chaotic layer micropore structure, so that the prepared soft carbon negative electrode material can accommodate more sodium ions, thereby improving the first coulombic efficiency and cycle stability of the sodium battery.
[0056] It should be noted that since the anthracite powder doped with oxygen-containing functional groups increases the interlayer spacing of the anthracite, heat can be transferred to the middle more quickly during step temperature carbonization. At the same time, combined with the pores on the surface, heat can flow more quickly from the multiple pores on the surface into the interior of the anthracite powder, thereby accelerating the carbonization rate of the anthracite powder doped with oxygen-containing functional groups. Furthermore, aluminum oxide, iron oxide and silicon oxide in the low ash content can disrupt the speed of heat transfer, thereby helping to construct a chaotic layer microporous structure inside.
[0057] S106, washing the anthracite carbonized material with water until it becomes neutral to obtain porous anthracite, so as to wash away excess impurities. Furthermore, deionized water is used for washing.
[0058] S107, mixing the porous anthracite with an alkaline solution to obtain a porous anthracite first mixed solution, so that the added alkaline solution can further etch the pores on the surface of the porous anthracite, which is helpful to construct a surface turbostratic microporous structure.
[0059] It can be understood that the present application uses two alkaline etchings. First, an alkaline solution is added in step S104 to achieve surface etching of the anthracite, which helps transfer the heat of the step temperature carbonization, thereby helping to construct a turbostratic microporous structure inside. Next, the porous anthracite is mixed with the alkaline solution to further etch the pores on the surface of the porous anthracite, which helps to construct a turbostratic microporous structure.
[0060] S108, adding an acid solution to the porous anthracite mixed solution to obtain a second porous anthracite mixed solution to further stabilize the turbostratic microporous structure.
[0061] S109, performing a heat preservation hydrothermal reaction on the porous anthracite second mixed liquid to obtain a porous anthracite third mixed liquid to better stabilize the turbostratic microporous structure. Further, in some other embodiments, the heat preservation hydrothermal reaction conditions are: temperature 100°C to 260°C, time 8h to 24h.
[0062] S110, filtering the porous anthracite third mixed liquid to obtain a precipitate.
[0063] S111, freeze-drying the precipitate to obtain the turbostratic microporous structure soft carbon negative electrode material.
[0064] The preparation method of the above-mentioned soft carbon negative electrode material with a turbostratic microporous structure can dope the anthracite powder with oxygen-containing functional groups by pre-oxidizing the anthracite powder. In this way, the doped oxygen-containing functional groups can increase the interlayer spacing of the anthracite, which is helpful to inhibit the directional growth of graphene domains during the subsequent step temperature carbonization to obtain a richer turbostratic microporous structure. The added alkaline solution can increase the porosity of the anthracite powder doped with oxygen-containing functional groups, and then the step temperature carbonization is performed, which is conducive to the formation of a relatively uniform and appropriately spaced soft carbon negative electrode material, thereby forming a rich turbostratic microporous structure. Figure 2 It can be seen that the soft carbon negative electrode material can accommodate more sodium ions, that is, it provides more sodium storage active sites for sodium ions, thereby enhancing the reversible capacity of the sodium battery, and further improving the first coulombic efficiency and cycle stability of the sodium battery. In addition, compared with the traditional method, the present application reduces the preparation process of the coating layer and avoids the addition of coating layer materials, thereby saving costs and giving full play to the advantages of carbon materials in sodium batteries to better adapt to market demand. Furthermore, since anthracite with an ash content of less than 3% is selected as the raw material to ensure that the impurities in the anthracite are moderate, it is helpful to construct a soft carbon negative electrode material with a rich chaotic layer microporous structure to improve the capacity of the soft carbon negative electrode material to accommodate sodium ions, thereby providing a good guarantee for the first coulombic efficiency and cycle performance of the sodium battery.
[0065] In some other embodiments, the anthracite powder is oxidized in an air atmosphere at 400°C to 500°C for 2h to 5h, and the air pressure is controlled to 3KPa to 5KPa to ensure that the interlayer spacing of 0.36nm to 0.4nm can be obtained through the above-mentioned pre-oxidation treatment conditions, so that the structure of the anthracite carbonized material is not prone to collapse during the subsequent step temperature carbonization. That is to say, when the interlayer spacing is greater than 0.4nm, its heat transfer rate is faster, and the structure of the anthracite carbonized material is prone to collapse. If the interlayer spacing is less than 0.36um, on the one hand, it is not conducive to the deintercalation of sodium ions, and on the other hand, it is not conducive to the rapid transfer of heat. Therefore, the present application performs oxidation treatment on the anthracite powder in an air atmosphere at 400°C to 500°C for 2h to 5h, and controls the air pressure to 3KPa to 5KPa to ensure that the interlayer spacing is relatively suitable. In this way, while ensuring that the conditions for sodium ion deintercalation are met, it also takes into account that the subsequent step temperature carbonization can construct a rich chaotic layer microporous structure, so that the prepared soft carbon negative electrode material can accommodate more sodium ions, thereby improving the first coulombic efficiency and cycle stability of the sodium battery. It should also be noted that when the interlayer spacing of the soft carbon negative electrode material is controlled to be 0.36nm to 0.4nm, the entire deintercalation spacing is biased towards the lower limit, so that the compaction density of the soft carbon negative electrode material of the same unit is relatively high, which is beneficial to improve the first coulombic efficiency and cycle stability of the sodium battery.
[0066] It should also be noted that since the anthracite is not coated in the present application, the interlayer spacing difference of the soft carbon negative electrode material cannot be increased to a significant extent, that is, when it is increased by 0.4nm, the interlayer spacing of the soft carbon negative electrode material is prone to collapse. Therefore, by controlling the interlayer spacing of the soft carbon negative electrode material to a lower limit of 0.36nm to 0.4nm, it can be ensured that the soft carbon negative electrode material has a better structure and is not prone to collapse.
[0067] For further information, see Figure 2 The turbostratic microporous structure is formed with multiple carbon layers, each of which forms a plurality of pores, and the pore volume of each pore is about 0.22 cm 3 / g, and the difference between the maximum pore volume and the minimum pore volume is not greater than 0.05cm 3 / g. In practical applications, when the difference between the maximum pore volume and the minimum pore volume is no more than 0.05cm3 / g, the first coulombic efficiency of the sodium battery decreases significantly, resulting in a decrease in the first coulombic efficiency of the sodium battery and poor cycle stability. Therefore, the pore volume of the turbostratic microporous structure controlled by this application is 0.22cm 3 / g, it can ensure that the pore volume difference of multiple holes in the chaotic layer microporous structure is small, and at the same time, with the interlayer spacing of 0.36nm to 0.4nm, the interlayer spacing of the chaotic layer microporous structure can be the same, and the pores of each layer are uneven, so that the chaotic layer microporous structure soft carbon negative electrode material can present a short-range ordered and long-range disordered structure, which is more conducive to the better deintercalation of sodium ions, thereby improving the first coulombic efficiency and cycle stability of sodium batteries. It is worth mentioning that the pore volume of each hole is 0.22cm 3 / g, and the difference between the largest hole and the smallest hole is no more than 0.05cm 3 / g, thereby ensuring that the pores of the turbostratic microporous structure are more suitable, so that the sodium ions can still maintain a good structure after repeated use, thereby ensuring the cycle stability of the sodium battery.
[0068] In some other embodiments, the step temperature carbonization conditions are: in an inert atmosphere, the temperature is increased to 800°C~1000°C at 3°C~8°C / min, then the temperature is increased to 1000°C~1400°C at 1°C~2°C / min and kept at this temperature for 2h~5h, then the temperature is decreased to 800°C~1000°C at 3°C~5°C / min, and then the temperature is decreased to room temperature at 5°C~8°C / min.
[0069] It can be understood that, first, the temperature is raised to 800°C to 1000°C at 3°C to 8°C / min, so as to ensure that the anthracite powder doped with oxygen-containing functional groups can be heated at a faster heating rate, that is, low-temperature rapid carbonization, and then the temperature is raised to 1000°C to 1400°C at 1°C to 2°C / min and kept for 2h to 5h to ensure that the anthracite powder doped with oxygen-containing functional groups can be heated at a slow heating rate, that is, high-temperature slow carbonization. The combination of low-temperature fast and high-temperature slow is conducive to the doping of oxygen-containing functional groups. The interlayer spacing of the clusters is expanded more evenly to ensure that carbonization forms a soft carbon with a more stable structure. At the same time, the combination of low temperature and high temperature helps to construct a rich chaotic layer microporous structure inside. Then the temperature is reduced to 800℃~1000℃ at 3℃~5℃ / min, and finally cooled to room temperature at 5℃~8℃ / min to ensure rapid cooling. This ensures that the anthracite powder doped with oxygen-containing functional groups has a certain heat difference, which helps to construct a chaotic layer microporous structure with a small pore size difference and rich.
[0070] In some other embodiments, the acid includes at least one of sulfuric acid, nitric acid, hydrofluoric acid and hydrochloric acid.
[0071] In some other embodiments, the alkaline solution includes at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide.
[0072] In order to ensure that anthracite with an ash content of less than 3% is obtained, in some other embodiments, the step of obtaining anthracite with an ash content of less than 3% also includes the following specific steps: acid washing the anthracite to remove impurities such as aluminum oxide and iron oxide; alkali washing the acid-washed anthracite to remove silicon oxide, so as to ensure that anthracite with an ash content of less than 3% is obtained.
[0073] Furthermore, in some other embodiments, the concentration of the acid used in the pickling is 3 mol / L to 5 mol / L. Furthermore, in a preferred embodiment, the acid is 4 mol / L hydrochloric acid.
[0074] Furthermore, in some other embodiments, the concentration of the alkali used in the alkali washing is 3 mol / L to 5 mol / L. Furthermore, in a preferred embodiment, the alkali is 4 mol / L sodium hydroxide.
[0075] Furthermore, in a preferred embodiment, the anthracite is pickled for 8 hours with a hydrochloric acid solution having a concentration of 4 mol / L, and then the pickled anthracite is alkaline washed for 8 hours with a sodium hydroxide solution having a concentration of 4 mol / L, to obtain anthracite with an ash content of less than 1%. When the anthracite with an ash content of less than 1% is subsequently pre-oxidized, the ash content is less than 1%, which can help to construct a rich turbulent layer microporous structure soft carbon negative electrode material, and then the rich turbulent layer microporous structure soft carbon negative electrode material can provide more active sites for sodium storage, thereby enhancing the reversible capacity of the sodium battery. Furthermore, the anthracite is Datong anthracite. The present application also provides a turbulent layer microporous structure soft carbon negative electrode material, which is obtained by the preparation method of the turbulent layer microporous structure soft carbon negative electrode material described in any of the above embodiments. Through this method, a layer spacing of 0.36nm to 0.4nm and a rich chaotic layer microporous structure can be obtained. Since anthracite with an ash content of less than 3% is selected as a raw material to ensure that the impurities in the anthracite are moderate, it is helpful to construct a soft carbon negative electrode material with a rich chaotic layer microporous structure to improve the capacity of the soft carbon negative electrode material to accommodate sodium ions, thereby providing a good guarantee for the first coulomb efficiency and cycle performance of the sodium battery. At the same time, the anthracite powder is pre-oxidized to allow the anthracite powder to be doped with oxygen-containing functional groups, so that the doped Oxygen-containing functional groups can increase the interlayer spacing of anthracite, which helps to inhibit the directional growth of graphene domains during subsequent step temperature carbonization to obtain a richer chaotic layer microporous structure. The added alkaline solution can increase the porosity of anthracite powder doped with oxygen-containing functional groups, and then step temperature carbonization is performed, which is conducive to the formation of a more uniform and appropriately spaced soft carbon negative electrode material, thereby forming a rich chaotic layer microporous structure. Therefore, the soft carbon negative electrode material can accommodate more sodium ions, thereby improving the first coulombic efficiency and cycle stability of the sodium battery. In addition, since the chaotic layer microporous structure soft carbon negative electrode material is not provided with a coating layer, the carbon material has a greater advantage in the sodium battery to better adapt to market demand, while avoiding the addition of coating layer materials, thereby saving costs.
[0076] The present application also provides a sodium battery, including the turbostratic microporous structure soft carbon negative electrode material described in any of the above embodiments. The turbostratic microporous structure soft carbon negative electrode material obtained in the present application is applied to the sodium battery. Since the turbostratic microporous structure soft carbon negative electrode material has a rich turbostratic microporous structure, it provides more sodium storage active sites for sodium ions, thereby enhancing the reversible capacity of the sodium battery, and further improving the first coulombic efficiency and cycle stability of the sodium battery.
[0077] Compared with the prior art, the present invention has at least the following advantages:
[0078] 1. The preparation method of the above-mentioned soft carbon negative electrode material with a microporous structure of a turbostratic layer can dope the anthracite powder with oxygen-containing functional groups by pre-oxidizing the anthracite powder. In this way, the doped oxygen-containing functional groups can increase the interlayer spacing of the anthracite, which is helpful to inhibit the directional growth of graphene domains during the subsequent step temperature carbonization to obtain a richer turbostratic microporous structure. The added alkaline solution can increase the porosity of the anthracite powder doped with oxygen-containing functional groups, and then step temperature carbonization is performed, which is conducive to the formation of a relatively uniform and appropriately spaced soft carbon negative electrode material, thereby forming a rich turbostratic microporous structure. Therefore, the hard carbon soft carbon negative electrode material can accommodate more sodium ions, that is, provide more sodium storage active sites for sodium ions, thereby enhancing the reversible capacity of the sodium battery, and then improving the first coulombic efficiency and cycle stability of the sodium battery. In addition, compared with the traditional method, the present application reduces the preparation process of the coating layer, avoids the addition of the coating layer material, thereby saving costs, and gives play to the advantages of carbon materials in sodium batteries to better meet market needs.
[0079] 2. The preparation method of the above-mentioned soft carbon negative electrode material with a turbostratic microporous structure selects anthracite with an ash content of less than 3% as the raw material to ensure that the impurities in the anthracite are moderate. This helps to construct a soft carbon negative electrode material with a rich turbostratic microporous structure to increase the capacity of the soft carbon negative electrode material to accommodate sodium ions, thereby providing a good guarantee for the first coulombic efficiency and cycle performance of the sodium battery.
[0080] Some specific examples are given below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.
[0081] Example 1
[0082] The Datong anthracite is pickled with a 4 mol / L hydrochloric acid solution for 8 hours, and then alkali-washed with a 4 mol / L sodium hydroxide solution for 8 hours to obtain anthracite with an ash content of <1%.
[0083] The anthracite is crushed to obtain anthracite powder; the anthracite powder is oxidized in an air atmosphere at 450° C. for 3 hours, and the air pressure is controlled to be 4 KPa, so as to dope the anthracite powder with oxygen-containing functional groups to obtain anthracite powder doped with oxygen-containing functional groups;
[0084] The anthracite powder doped with oxygen-containing functional groups and a sodium hydroxide solution are mixed in a ratio of 1:3 to obtain an anthracite mixed solution;
[0085] The anthracite mixture is subjected to step-temperature carbonization to obtain anthracite carbonized material, wherein the step-temperature carbonization conditions are: in an inert atmosphere, the temperature is increased to 900°C at 5°C / min, then the temperature is increased to 1200°C at 2°C / min and kept at that temperature for 3 hours, then the temperature is decreased to 900°C at 3°C, and then the temperature is decreased to room temperature at 6°C;
[0086] The anthracite carbonized material is washed with deionized water until it is neutral to obtain porous anthracite; the porous anthracite is mixed with a sodium hydroxide solution to obtain a porous anthracite first mixed liquid; a sulfuric acid solution is added to the porous anthracite mixed liquid to obtain a porous anthracite second mixed liquid; the porous anthracite second mixed liquid is subjected to a hydrothermal reaction at 200°C for 12 hours to obtain a porous anthracite third mixed liquid; the porous anthracite third mixed liquid is filtered to obtain a precipitate; the precipitate is freeze-dried to obtain the chaotic layer microporous structure soft carbon negative electrode material.
[0087] Example 2
[0088] The Datong anthracite was acid-washed with a 3 mol / L nitric acid solution for 8 hours, and then alkaline-washed with a 3 mol / L potassium hydroxide solution for 8 hours to obtain anthracite with an ash content of 2.8%.
[0089] The anthracite is crushed to obtain anthracite powder; the anthracite powder is oxidized in an air atmosphere at 400° C. for 2 hours, and the air pressure is controlled to be 3 KPa, so that the anthracite powder is doped with oxygen-containing functional groups to obtain anthracite powder doped with oxygen-containing functional groups;
[0090] The anthracite powder doped with oxygen-containing functional groups and a sodium hydroxide solution are mixed in a ratio of 1:1 to obtain an anthracite mixed solution;
[0091] The anthracite mixture is subjected to step-temperature carbonization to obtain anthracite carbonized material, wherein the step-temperature carbonization conditions are: in an inert atmosphere, the temperature is increased to 800°C at 3°C / min, then the temperature is increased to 1000°C at 1°C / min and kept at that temperature for 5 hours, then the temperature is decreased to 1000°C at 4°C, and then the temperature is decreased to room temperature at 5°C;
[0092] The anthracite carbonized material is washed with deionized water until it is neutral to obtain porous anthracite; the porous anthracite is mixed with a sodium hydroxide solution to obtain a porous anthracite first mixed liquid; a sulfuric acid solution is added to the porous anthracite mixed liquid to obtain a porous anthracite second mixed liquid; the porous anthracite second mixed liquid is subjected to a hydrothermal reaction at 100°C for 24 hours to obtain a porous anthracite third mixed liquid; the porous anthracite third mixed liquid is filtered to obtain a precipitate; the precipitate is freeze-dried to obtain the turbostratic microporous structure soft carbon negative electrode material.
[0093] Example 3
[0094] The Datong anthracite was pickled with a 5 mol / L hydrochloric acid solution for 8 hours, and then alkali-washed with a 5 mol / L sodium hydroxide solution for 8 hours to obtain anthracite with an ash content of 1.5%.
[0095] The anthracite is crushed to obtain anthracite powder; the anthracite powder is oxidized in an air atmosphere at 500° C. for 3 hours, and the air pressure is controlled to be 5 KPa, so as to dope the anthracite powder with oxygen-containing functional groups to obtain anthracite powder doped with oxygen-containing functional groups;
[0096] The anthracite powder doped with oxygen-containing functional groups and a sodium hydroxide solution are mixed in a ratio of 1:5 to obtain an anthracite mixed solution;
[0097] The anthracite mixture is subjected to step-temperature carbonization to obtain anthracite carbonized material, wherein the step-temperature carbonization conditions are: in an inert atmosphere, the temperature is increased to 1000°C at 8°C / min, then the temperature is increased to 1400°C at 2°C / min and kept at that temperature for 2h, then the temperature is decreased to 1000°C at 5°C, and then the temperature is decreased to room temperature at 8°C;
[0098] The anthracite carbonized material is washed with deionized water until it is neutral to obtain porous anthracite; the porous anthracite is mixed with a sodium hydroxide solution to obtain a porous anthracite first mixed liquid; a sulfuric acid solution is added to the porous anthracite mixed liquid to obtain a porous anthracite second mixed liquid; the porous anthracite second mixed liquid is subjected to a hydrothermal reaction at 260° C. for 8 hours to obtain a porous anthracite third mixed liquid; the porous anthracite third mixed liquid is filtered to obtain a precipitate; the precipitate is freeze-dried to obtain the chaotic layer microporous structure soft carbon negative electrode material.
[0099] Comparative Example 1
[0100] The difference from Example 1 is that, in Example 1, the step of "pickling the Datong anthracite with a hydrochloric acid solution having a concentration of 4 mol / L for 8 hours, and then alkali-washing the acid-washed Datong anthracite with a sodium hydroxide alkaline solution having a concentration of 4 mol / L for 8 hours to obtain anthracite with an ash content of <1%" is omitted, and the rest remains unchanged.
[0101] Comparative Example 2
[0102] The difference from Example 1 is that the oxidation treatment step of Example 1 is omitted in Comparative Example 2, and the rest remains unchanged.
[0103] Comparative Example 3
[0104] The difference from Example 1 is that the step temperature carbonization conditions of Comparative Example 3 are different, that is, the step temperature carbonization conditions of Comparative Example 3 are: in an inert atmosphere, heating to 1200°C at 5°C / min and keeping warm for 3h, then cooling to room temperature at 3°C, and the rest remain unchanged.
[0105] The turbostratic microporous soft carbon negative electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 are applied to sodium batteries, and the test results shown in Table 1 are as follows:
[0106] Table 1
[0107]
[0108]
[0109] From the comparison between Examples 1 to 3 and Comparative Examples 1 to 3, it can be seen that since Examples 1 to 3 use anthracite with an ash content of less than 3% as raw material, and cooperate with pre-oxidation and step temperature carbonization treatment, a relatively uniform and appropriately spaced turbostratic microporous structure soft carbon negative electrode material can be obtained, that is, the first coulomb efficiency reaches more than 83.96%, and the capacity retention rate reaches more than 86.17%, which is significantly better than Comparative Examples 1 to 3. In particular, the comprehensive indicators of Example 1 are the best, please refer to Figures 3 to 5 From the test graph of the first coulomb efficiency of the turbostratic microporous structure soft carbon negative electrode material, it can be seen that the first coulomb efficiency of the turbostratic microporous structure soft carbon negative electrode material of Example 1 is 85.44%, and Figure 6 It can be seen that the capacity retention rate of the turbostratic microporous structure soft carbon negative electrode material of Example 1 is 89.06%.
[0110] from Figure 6 and Figure 7 As shown in Table 1, since the Datong anthracite in Comparative Example 1 was not subjected to acid-base treatment, the ash content of the Datong anthracite in Comparative Example 1 was relatively high, that is, the ash content was higher than 3%, so that the first coulombic efficiency and capacity retention rate of Comparative Example 1 were worse than those of Example 1.
[0111] from Figure 6 and Figure 8 As shown in Table 1, since the Datong anthracite is not oxidized in Comparative Example 2, the first coulombic efficiency and capacity retention rate of Comparative Example 2 are worse than those of Example 1.
[0112] from Figure 6 and Fig. 9 As shown in Table 1, since Comparative Example 3 does not perform step-temperature carbonization on Datong anthracite, the first coulombic efficiency and capacity retention rate of Comparative Example 3 are worse than those of Example 1.
[0113] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as a restriction on the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a turbostratic microporous structure soft carbon negative electrode material, characterized in that: The steps include: Obtain anthracite with an ash content of less than 3%; wherein the anthracite is pickled for 8 hours, and the acid used for the pickling is 3mol / L to 5mol / L hydrochloric acid; the pickled anthracite is alkali washed for 8 hours, and the alkali used for the alkali washing is 3mol / L to 5mol / L sodium hydroxide, so as to obtain anthracite with an ash content of less than 3%; When the ash content of anthracite is less than 3%, the aluminum oxide, iron oxide and silicon oxide in the low ash content can disrupt the speed of heat transfer, so as to help construct a soft carbon negative electrode material with rich turbostratic microporous structure; The anthracite is crushed to obtain anthracite powder; wherein the particle size of the anthracite powder is 5 μm to 30 μm; The anthracite powder is subjected to oxidation treatment in an air atmosphere at 400° C. to 500° C. for 2 h to 5 h, and the air pressure is controlled to be 3 KPa to 5 KPa, so as to dope the anthracite powder with oxygen-containing functional groups to obtain anthracite powder doped with oxygen-containing functional groups; The anthracite powder doped with oxygen-containing functional groups is mixed with an alkali solution to obtain an anthracite mixed solution; wherein the mass ratio of the anthracite powder doped with oxygen-containing functional groups to the alkali solution is 1:1 to 1:5; The anthracite mixture is subjected to step temperature carbonization to obtain anthracite carbonized material; wherein the step temperature carbonization conditions are: in an inert atmosphere, the temperature is increased to 800°C~1000°C at 3°C~8°C / min, then the temperature is increased to 1000°C~1400°C at 1°C~2°C / min and kept at this temperature for 2h~5h, then the temperature is decreased to 800°C~1000°C at 3°C~5°C / min, and then the temperature is decreased to room temperature at 5°C~8°C / min; the anthracite carbonized material is washed with water until it is neutral to obtain porous anthracite; Mixing the porous anthracite with an alkaline solution to obtain a first porous anthracite mixed solution; adding an acid solution to the porous anthracite first mixed liquid to obtain a porous anthracite second mixed liquid; The porous anthracite second mixed liquid is subjected to a heat preservation hydrothermal reaction to obtain a porous anthracite third mixed liquid; wherein the heat preservation hydrothermal reaction conditions are: temperature 100° C. to 260° C., time 8 h to 24 h; filtering the porous anthracite third mixed liquid to obtain a precipitate; The precipitate is freeze-dried to obtain the turbostratic microporous structure soft carbon negative electrode material, so that the turbostratic microporous structure soft carbon negative electrode material can present a short-range ordered and long-range disordered structure.
2. The method for preparing a turbostratic microporous structure soft carbon negative electrode material according to claim 1, characterized in that: The acid in the acid solution includes at least one of sulfuric acid, nitric acid, hydrofluoric acid and hydrochloric acid.
3. The method for preparing a turbostratic microporous structure soft carbon negative electrode material according to claim 1, characterized in that: The alkaline solution includes at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide.
4. A turbostratic microporous structure soft carbon negative electrode material, characterized in that: The method for preparing the turbostratic microporous structure soft carbon negative electrode material according to any one of claims 1 to 3 is used to obtain the material.
5. A sodium battery, characterized in that: It includes the turbostratic microporous structure soft carbon negative electrode material as described in claim 4.
Citation Information
Patent Citations
Method for preparing modified graphite negative electrode material of sodium ion battery
CN104377346A
Polyimide-based porous carbon film prepared by using silicon dioxide as template and preparation method thereof
CN107253710A
Method for synthesis of biomass carbon material from cassia tree leaves by hard template process and application
CN109019553A
Carbon material for sodium-ion battery negative electrode, preparation method of carbon material, sodium-ion battery negative electrode plate and sodium-ion battery
CN114956037A